Solomon Islands Student Assessment : SABER Country Report 2014 - World Bank Group (World Bank, Washington, DC, 2016)
The Solomon Islands has focused on increasing studentlearning outcomes by improving the quality of educationin the country. An effective student assessment systemis an important component of efforts to improveeducation quality and learning outcomes because itprovides the necessary information to meet stakeholders’ decision-making needs. In order to gain abetter understanding of the strengths and weaknesses ofits existing assessment system, the Solomon Islands decided to benchmark this system using standardized tools developed under The World Bank’s Systems Approach for Better Education Results (SABER) program.SABER is an evidence-based program to help countriessystematically examine and strengthen the performanceof different aspects of their education systems. The goal ofSABER-Student Assessment is to promote stronger assessment systems that contribute to improved education quality and learning for all.